EXPLORING THE POTENTIAL AND CONSEQUENCES OF AI AND CHATGPT IN EDUCATIONAL SETTINGS (Web of Teachers: Inderscience Research, 2025)
The central question of this article is formulated as follows: "What opportunities and challenges are emerging from the development and implementation of artificial intelligence systems within the educational environment?" To explore this question, the present thesis employs a narrative review method, analyzing current research, perspectives, and scholarly literature on AI and ChatGPT (and, in a broader context, on AI and large language models — LLMs).